A Novel Use of Allopurinol as A Quorum-Sensing Inhibitor in Pseudomonas aeruginosa - Ahmed Al Saqr; Mohammed F. Aldawsari; El-Sayed Khafagy; Moataz A. Shaldam; Wael A. H. Hegazy; Hisham A. Abbas (MDPI AG, 2021)
Pseudomonas aeruginosa can cause a variety of healthcare-associated infections by its arsenal of virulence factors. Virulence factor production is largely controlled by the cell-to-cell communication system termed quorum sensing (QS). Targeting QS may be a good approach to inhibit the production of virulence factors and attenuate pathogenicity without exerting selective stress on bacterial growth. This will greatly reduce the emergence of resistant mutants. In this work, we investigated the anti-virulence and anti-QS activities of the FDA-approved drug allopurinol against the P. aeruginosa PAO1 strain. Allopurinol at 200 µg/mL (1/10 MIC) significantly decreased the production of the QS-controlled Chromobacterium violaceum CV026 violet pigment violacein and other P. aeruginosa QS-controlled virulence factors phenotypically. Furthermore, allopurinol reduced the infiltration of P. aeruginosa and leucocytes and diminished the congestion in the liver and kidney tissues of infected mice. In silico study showed that allopurinol could compete with the autoinducers on binding to the receptors LasR and RhlR by hydrogen bonding. On the molecular level, qRT-PCR proved that allopurinol showed a significant downregulating effect on all tested QS-encoding genes that regulate virulence factor production. In summary, allopurinol is a promising QS inhibitor that may be useful in the future treatment of P. aeruginosa infection.